High Capacity All‐Solid‐State Lithium Batteries Enabled by Pyrite‐Sulfur Composites. Issue 26 (18th July 2018) - Ulissi, Ulderico; Ito, Seitaro; Hosseini, Seyed Milad; Varzi, Alberto; Aihara, Yuichi; Passerini, Stefano
Abstract: As the theoretical limit of intercalation material‐based lithium‐ion batteries is approached, alternative chemistries based on conversion reactions are presently considered. The conversion of sulfur is particularly appealing as it is associated with a theoretical gravimetric energy density up to 2510 Wh kg −1 . In this paper, three different carbon‐iron disulfide‐sulfur (C‐FeS2 ‐S) composites are proposed as alternative positive electrode materials for all‐solid‐state lithium‐sulfur batteries. These are synthesized through a facile, low‐cost, single‐step ball‐milling procedure. It is found that the crystalline structure (evaluated by X‐ray diffraction) and the morphology of the composites (evaluated by scanning electron microscopy) are greatly influenced by the FeS2 :S ratio. Li/LiI‐Li3 PS4 /C‐FeS2 ‐S solid‐state cells are tested under galvanostatic conditions, while differential capacity plots are used to discuss the peculiar electrochemical features of these novel materials. These cells deliver capacities as high as 1200 mAh g(FeS2+S) −1 at the intermediate loading of 1 mg cm −2 (1.2 mAh cm −2 ), and up to 3.55 mAh cm −2 for active material loadings as high as 5 mg cm −2 at 20 °C. Such an excellent performance, rarely reported for (sulfur/metal sulfide)‐based, all solid‐state cells, makes these composites highly promising for real application where high positive electrode loadings are required. Abstract : An all‐solid‐state Li‐S battery with high active material loading and a lithium negative electrode is demonstrated. LiI‐Li2 S‐P2 S5 is used as the electrolyte and various sulfur‐iron disulfide‐carbon composites as positive electrodes, prepared by using mechanochemical synthesis. The beneficial effect of incremental sulfur addition during synthesis is demonstrated, leading to stable reversible capacities over 3.5 mAh cm −2 when the pyrite phase is stabilized.